KARYA SENI INDONESIA SEBAGAI OBJEK PERLINDUNGAN HAK CIPTA: JANGKAUAN DAN PERMASALAHAN - Djoko Saryono (Imaji, 2007)
As an intellectual creation, arts have long become the objects of copyright protection. International copyright regulations have been legislated and many have been ratified. Indonesia has also established such regulations as well as ratified the international patent laws to protect art works. The regulations are relatively adequate, however, the implementation and the control are still very bad. Key words: arts works, protection, and copyright